Is There a Diagnostic and Prognostic Role for Anti-Nephrin Autoantibodies in Diabetic Nephropathy? - Han Sean Lee; Henry H. L. Wu; Arvind Ponnusamy; Helen Alderson; Rajkumar Chinnadurai (Antibodies)
Diabetic nephropathy (DN) is one of the key causes of end-stage kidney disease worldwide, especially in developed countries. The classic pathogenic development of DN is characterized by microalbuminuria which would progress to nephrotic-range proteinuria and loss of kidney function. The degree of albuminuria is considered an independent risk factor for all-cause mortality in patients with DN. It is now well established that albuminuria stems from disruptions in podocyte structure and function. Podocytes play a major role in the glomerular filtration barrier. The nephrin protein has been identified as a core component of the slit diaphragm in podocytes, and as such, the downregulation of nephrin expression has been described well in various proteinuric glomerulopathies, including DN. Previous studies have shown that the presence of urinary nephrin potentially signifies an early marker of podocyte injury in DN. More recently, there have been increasing bodies of evidence which suggest that circulating autoantibodies targeting nephrin contributes to the pathogenesis of podocytopathies. However, the functional significance of these circulating autoantibodies in patients with DN is not well understood. In this review, we aim to evaluate the significance of nephrin dysregulation in the pathogenesis of DN based on the current available literature and provide an overview on the application of circulating anti-nephrin autoantibodies in relation to its diagnostic as well as prognostic role in podocytopathies, including DN.